NUTRITIONAL ANALYSIS OF EDIBLE WILD PLANTS USED BY HAKKI PIKKI TRIBES OF HASSAN DISTRICT, KARNATAKA, INDIA - Kumar, Gotruvalli Manjunatha Prashanth; Chikkapaih, Lava; Nagayya, Shiddamallayya (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
Objective: The aim of the study was to determine the nutritional composition of wild edible leaves, tubers, fruit and young shoot consumed by Hakki Pikki tribals of Hassan district. Methods: The samples were analyzed for proximate nutritional composition (moisture, ash, proteins, carbohydrates, crude fat and crude fiber) using the AOAC procedures. The minerals were determined by using atomic absorption spectrophotometer. Results: Moisture content of the analyzed samples were ranged between 75.8Â±3.1 and 64.3Â±1.4g/100g with the highest being in a fruit of Momordica dioica (75.8Â±3.1g/100g) carbohydrate content found maximum in 23Â±2.1g/100g in tuber of Dioscorea oppositifolia. The high content of vitamin-C in the fruit of Momordica dioica (77.1Â±11.9g/100g), the nutritive value was found highest in tuber of Dioscorea oppositifolia (130.40 kal/100g). The corm of Colocasia esculenta contained 326.7Â±7.6 mg/100g of the magnesium and considered a good source. The iron content in tender leaves of Alternanthera sessilis (14.3Â±1.8 mg/100g) was estimated to have maximum iron content. Conclusion: Analysis of eight wild edible plants emphases the rich nutritional composition and their scope to be used as an alternate source of bio-nutrient.Â